Effectiveness of Feedback with Mobile Devices for Quality Measure of CPR Training: A Systematic Review - Vitasari, Imaniar; Awaludin, Sidik; Pratama, Koernia Nanda (Indonesian Journal of Global Health Research, 2024)
Cardiopulmonary resuscitation (CPR) is a life-saving skill that can significantly increase survival rates in an emergency. Medical professionals, health students, and trained lay people must all perform high-quality CPR. As an outcome, effective CPR training using instruments that support the achievement of high-quality CPR is essential. Objective: This systematic review aimed to evaluate the effectiveness of feedback provided via mobile devices in measuring the quality of CPR training. Method: Design used systematic review with reference to the PRISMA Statement Guidelines 2020. Search results through database of ScienceDirect (778 articles), Wiley Online Library (765 articles), PubMed (55 articles), and ResearchGate (73 articles). The research designs of articles analyzed was randomized controlled trial which published from 2013 to 2023 with the keywords cardiopulmonary resuscitation, CPR training, mobile devices. The sample in this study was taken from five articles that match the inclusion criteria. JBI's critical assessment tool for assessing bias risk in randomly controlled 2023 checklist tests is used to critically evaluate the instruments used for the selected article. Results: The primary results that five publications were based on CPR quality metrics such as chest compression depth and speed, as well as the proportion of acceptable chest compression depth. Conclusions: This review discovered evidence that mobile devices have an effect on the effectiveness of real-time feedback on CPR quality in CPR training. CPR trainees received effective instant guidance from a variety of mobile devices, including smartphones and smart watches equipped with sensors.